PENERAPAN STRATEGI PEMBELAJARAN THE FIRING LINE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 2 TAMBANG. - Rahmadani '; R Usman Rery; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to increase student achievementon the subject Atomic Structure and System of Periodic unsure inclass X SMA Negeri 2 Tambang. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMA Negeri 2 Tambang. The samples of this research were the students of class X.5 as the experimental class and students of class X.6 as the control class.Experimental class is a class that is applied learning strategy The Firing Line, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 1,70 > 1,67, ). It means that the application of learning strategy The Firing Line can improve student’s achievement on the topic of atomic structure and system of periodic unsure inclass X SMA Negeri 2 Tambang. The improvement of student’s achievement in experiment class was supported by N-Gain score 0,75 that included in high category.Keywords : Learning Achievement, Learning Strategy The Firing Line, and Atomic Structure and System of Periodic unsure